Love Practices in the Colombian School during the First Half of the Twentieth Century: Notes for a History of Feminine Love - Claudia Ximena Herrera Beltrán (Universidad Pedagógica Nacional, 2016)
In Latin America women increasingly detach themselves from feminine representations produced by certain discourses of modernity. However, unequal relations, binary constructions of sex and gender, and exclusion whenever there is any sign of resistance are still signs of contemporaneity. In response to this situation, this research paper shows, through an archaeological and genealogical study, how love, as a feeling and emotion, was a subject of education for girls in the Colombian school during the first half of the twentieth century. In that sense, the author reflects upon emotions, feelings and discourses, and reveals how society shaped practices and legitimized truths that, even today, define both men's and women's nature.